Polityczne uwarunkowania utworzenia i działalności przysposobienia rolniczo-wojskowego młodzieży (1947–1948) - Lesiakowski, Krzysztof (Zeszyty Wiejskie, 2016)
During World War I and II not only the army but the whole nations were fighting. Therefore, military training involving all society, especially the young people, was necessary. During the interwar period in Poland the military training of youth was developing but it never had universal character. After the ending of World War II the idea of involving all young people in military training was instigated in Poland again. One of the instruments of this policy was Military-Agricultural Training of youth. This postulate was not realized because the project did not obtain political support, primarily the resistance of Polish village youth was not broken down, before engagement in this political action. Therefore, in 1948 the Common Organization “Service for Poland” was created. It was a new form of military training of Polish youth.